Multi-parametric MRI of the Prostate Aids to Detect Lesion Progression: Case Report - Johnson, Linda M. (2014)
Multi-parametric MRI (MP-MRI) provides an accurate anatomical assessment of the tumor and its local staging. Herein we report a case of intermediate risk prostatic adenocarcinoma, initially followed on active surveillance, which upgraded from Gleason 7 (3+4) to Gleason 8 (4+4) on transrectal ultrasound/MRI (TRUS/MRI) fusion biopsy after progression of MR spectroscopic findings and review the role of MP-MRI in the follow-up of prostate cancer patients undergoing active surveillance.